PENGARUH PROFITABILITY, ASSET TANGIBILITY, DAN INSTITUTIONAL OWNERSHIP TERHADAP STRUKTUR MODAL DAN DAMPAKNYA PADA KEBIJAKAN DIVIDEN (Studi pada Industri Manufaktur di Bursa Efek Indonesia Periode Tahun 2009-2011) - Wardhana, Guruh Hanityo (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2012)
This research was performed to investigate the influence of profitability, asset tangibility and institutional ownership on capital structure and dividend policy at manufacturing company published financial report during period 2009 - 2011.The sample of this research was selected based on purposive sampling with the following criteria: (1) manufacturing company published financial report during period2009 - 2011; and (2) manufacturing company given dividend during period 2009 -2011. The Data was based on publicity Indonesian Capital Market Directory (ICMD) from2009 to 2011. Sample was acquired 31 of 159 company. Data was analyzed with multi linier regression of ordinary least square and hypotheses was tested using t-statistic and f-statistic at level of significance 5%.Empirical evidence showed that profitability and asset tangibility had significant influence on capital structure of manufacturing company listed in IDX over period 2009-2011 at level of significance less than 5%, and capital structure,Â profitability and asset tangibility had significant influence on dividend policy of manufacturing company listed in IDX over period 2009-2011 at level of significance less than 5%.